2001
DOI: 10.4049/jimmunol.166.3.2002
|View full text |Cite
|
Sign up to set email alerts
|

Fibrinogen Promotes Neutrophil Activation and Delays Apoptosis

Abstract: The acute phase of the inflammatory response involves an increase in the concentrations of different plasma proteins that include fibrinogen (Fbg) and multiple proinflammatory mediators. In parallel, neutrophil activation is thought to play a crucial role in several inflammatory conditions, and it has been recently demonstrated that Fbg specifically binds to the α-subunit of CD11b/CD18 on neutrophil surface. Although several reports have shown that CD11b engagement modulates neutrophil responses, the effect of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
95
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 122 publications
(105 citation statements)
references
References 59 publications
10
95
0
Order By: Relevance
“…However, exposure to sFbg or cytokines such as GM-CSF and IL-6 has been shown to delay apoptosis (7,54,55), thereby contributing to host defense or, under other circumstances, tissue injury. It has been previously reported that ERK MAPK pathway is involved in cell survival and preventing or delaying apoptosis (56 -58).…”
Section: Discussionmentioning
confidence: 99%
“…However, exposure to sFbg or cytokines such as GM-CSF and IL-6 has been shown to delay apoptosis (7,54,55), thereby contributing to host defense or, under other circumstances, tissue injury. It has been previously reported that ERK MAPK pathway is involved in cell survival and preventing or delaying apoptosis (56 -58).…”
Section: Discussionmentioning
confidence: 99%
“…Fibrinogen has been determined to be involved in the acute inflammatory response phase, activating neutrophil markers that cause an increase in phagocytosis, cellular cytotoxicity and apoptosis delay [139]. Therefore, reduced amounts of fibrinogen for surgical procedures are recommended to prevent additional inflammatory reactions.…”
Section: Safety Of Fibrin Gluementioning
confidence: 99%
“…Because adherent neutrophils respond differently to TNF-␣ than those in suspension, it is possible that input from integrin-activated signaling may have a critical role in regulating TNF-␣-mediated antiapoptotic signaling. Indeed, different extra-cellular matrix proteins have disparate effects on neutrophil spontaneous apoptosis and may have an important role in regulating TNF-␣ antiapoptotic and proapoptotic signaling (47,56).…”
mentioning
confidence: 99%